1998
DOI: 10.1046/j.1432-1327.1998.2530734.x
|View full text |Cite
|
Sign up to set email alerts
|

The 58‐kDa microspherule protein (MSP58), a nucleolar protein, interacts with nucleolar protein p120

Abstract: Protein p120 is a proliferation-related nucleolar protein which is detectable early in the G1 phase of the cell cycle and peaks early in the S phase. Most human malignant tumors contain much higher levels of protein p120 than normal resting cells. To identify p120-associated protein(s), a yeast two-hybrid screen was carried out using protein p120 as the bait. Two positive clones encoded portions of a novel protein, designated microspherule protein 58 kDa (MSP58). MSP58 mRNA is 1.9 kb and encodes an approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 6 publications
2
57
1
Order By: Relevance
“…Figure 2) revealed apparent similarities to human sequences corresponding to the microspherule protein 1 (MCRS1) p78 (Bruni and Roizman, 1998), also designated as 58-kDa microspherule protein MSP58 (Ren et al, 1998) (Table 1). The MCRS1 protein is located in cellular nucleoli where it interacts with the nuclear regulatory protein ICP22 from herpes simplex virus 1, and accumulates in a cell cycle-dependent manner (Bruni and Roizman, 1998).…”
Section: The Protein Product Of Toj3 Is Related To Nucleolar Proteinsmentioning
confidence: 76%
See 3 more Smart Citations
“…Figure 2) revealed apparent similarities to human sequences corresponding to the microspherule protein 1 (MCRS1) p78 (Bruni and Roizman, 1998), also designated as 58-kDa microspherule protein MSP58 (Ren et al, 1998) (Table 1). The MCRS1 protein is located in cellular nucleoli where it interacts with the nuclear regulatory protein ICP22 from herpes simplex virus 1, and accumulates in a cell cycle-dependent manner (Bruni and Roizman, 1998).…”
Section: The Protein Product Of Toj3 Is Related To Nucleolar Proteinsmentioning
confidence: 76%
“…Aberrant migration has been also observed for the 462-amino acid MSP58 protein migrating with an apparent size of 58 kDa (Ren et al, 1998), and for the 534-amino acid MCRS1 (p78) protein with migration sizes of 78, 62 and 55 kDa (Bruni and Roizman, 1998). Apart from the 84 amino terminal residues, TOJ3 is highly related to the mammalian MCRS1 proteins and thus may represent the MCRS1 quail ortholog (cf.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MSP58 was first identified as a nuclear protein that interacts with the proliferation-related nucleus protein p120 (Ren et al, 1998). Additional studies showed that, in the nucleus, MSP58 could function to regulate transcription through its interactions with the transcription factors Daxx, STRA13, and the RNA-binding protein FMR (Lin et al, 2002;Ivanova et al, 2005;Davidovic et al, 2006).…”
mentioning
confidence: 99%